Efektivitas Media Evaluasi Quizizz Mode Paper terhadap Peningkatan Hasil Belajar Siswa pada Materi Pengurangan - Nailan, Akhmaliah Siti; Hodijah, Anisa Siti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Education is an important asset in the development of the country, whose success can be measured through student learning outcomes. Subtraction material in grade 1 SD has a fundamental role in learning mathematics, although many students face difficulties in understanding it. This study aims to analyze the effectiveness of Quizizz Mode Paper evaluation media in improving student learning outcomes on subtraction material. The study used a pre-experimental experimental design with a One-Group Pretest-Posttest Design approach, involving 21 grade 1 elementary school students selected by simple randomization. Data were collected through tests before and after treatment, then analyzed using descriptive and inferential statistics. The results showed an increase in the average score from 79.95 to 91.43, with an N-Gain value of 64%. Wilcoxon test showed a significant difference (p<0.05), and regression analysis showed that this media contributed 61.2% to the improvement of learning outcomes. Quizizz Mode Paper proved to be effective and relevant as an interactive learning media that supports students' understanding of basic math concepts.